Análise do processo de gestão estratégica de custos e formação de preço, no âmbito do jogo de empresas, com apoio de treinamento baseado no computador (CBT) - Madkur, Federico Natalio (2008)
In the present work, seeking to explore the effects of integration of learning tools, it tried to analyze the impact of the availability and use of training based in computer (CBT) within the experience of business games. Was compared in the study, the economical performance and the consistence of the strategic alignment of the simulated companies in the business games SEE (Simulação de Estratégia Empresarial), for which was made available a CBT of strategic management of costs and formation of prices, with the same indicators obtained by simulated companies in previous editions of the game SEE, accomplished in the last six years, in the degree and post-graduation courses in administration of UEL. For the analysis, the data were separated due to the different sceneries for the editions of the business game SEE and levels of formation of the students researched. About the methodology, it is characterized as a quantitative method, experimental research and with analysis of the contribution noticed by the students, by the use of CBT as survey, with the cut of the research of sectional type with longitudinal perspective. For the analysis of the results, statistical techniques were used, and for validation of the formulated hypotheses were applied the tests t-student and Mann Whitney. The main results of the research were: the return of the operational assets and the cumulative growth of the equity were influenced by the use of CBT in the degree students in the scenery A; in the scenery B and for the students of post-graduation the results did not present variability. As for the students' perception in relation to the use of CBT, it was concluded that: the CBT presented high benefits in the integration of knowledge, it aided in practice of making decisions and analysis of problems, it contributed to the teaching/learning, it demonstrated larger effectiveness in relation to the traditional methods of teaching and it integrated the theory and practice of the specific content presented. Although there have been improvements in the indicators of economical performance, in the simulated companies with the readiness and use of CBT, it was not possible to affirm, statistically, that they make an impact in the results. But the students' positive appreciation who used CBT indicated that the tool is effective in the aid for professional formation. However, by the results of the study, it is not possible to confirm that its integration with the business games can potentiate their benefits